Ultrasonographic features of cutaneous myxomas in a patient with Carney complex, - Monica Quintana-Codina; Marina Corral-Forteza; Maribel Iglesias-Sancho; Montse Salleras-Redonnet (Sociedade Brasileira de Dermatologia, 2022)
Abstract Carney complex is a rare genodermatosis characterized by cardiac and cutaneous myxomas, among other tumors. In the majority of cases, cutaneous myxomas precede the diagnosis of cardiac myxomas, which are the main cause of death in these patients. Despite the fact that the diagnosis of cutaneous myxomas is histopathological, high-frequency ultrasonography plays an essential role in the differential diagnosis with other cutaneous and subcutaneous tumors. The authors of the present study describe, for the first time in the literature, the ultrasonographic features of both variants of cutaneous myxomas, superficial and subcutaneous, in a patient with a Carney complex.